2021
DOI: 10.1007/s13304-021-01182-5
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcomes of sleeve gastrectomy as a revisional procedure after failed gastric band: a multicenter cross-matched cohort study

Abstract: Laparoscopic adjustable gastric band (LAGB) is the bariatric procedure most likely subject to revisional surgery. Both laparoscopic sleeve gastrectomy (LSG) and Roux-en-Y gastric bypass (LRYGB) represent viable options, but the long-term results are still lacking. In 2014, we published the 2-year follow-up of our multicenter cohort of revisional LSG after failed LAGB. Evaluate the long-term follow-up (median 9.3 years) of the same cohort of patients. University and primary-care hospitals, Italy. We retrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 23 publications
3
6
0
Order By: Relevance
“…While Carandina et al’s study suggested that rLSG resulted in somewhat lower AMP remission/improvement than pLSG, our study more closely mirrored the findings of Kraljevic et al and De Angelis et al [ 37 39 ], which reported equally durable weight loss and AMP control between pLSG and rLSG patients. Kraljević et al’s study showed considerable AMP improvement in pLSG and rLSG patients combined: T2DM 61.0%, hypertension 60.5%, and hyperlipidemia 46.0%, findings comparable to our own study.…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…While Carandina et al’s study suggested that rLSG resulted in somewhat lower AMP remission/improvement than pLSG, our study more closely mirrored the findings of Kraljevic et al and De Angelis et al [ 37 39 ], which reported equally durable weight loss and AMP control between pLSG and rLSG patients. Kraljević et al’s study showed considerable AMP improvement in pLSG and rLSG patients combined: T2DM 61.0%, hypertension 60.5%, and hyperlipidemia 46.0%, findings comparable to our own study.…”
Section: Discussionsupporting
confidence: 89%
“…In addition to the three currently available long-term reports of post-LSG weight loss [ 37 39 ], the current study’s primary group EWL outcomes were > 50.0%, falling within the range of the four study results (51.0 to 67.0%). The current study’s revisional group EWL outcomes also fell within the range of the four studies (29.8 to 53.0% EWL).…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations